Anti-Gr-1 antibody depletion fails to eliminate hepatic myeloid-derived suppressor cells in tumor-bearing mice - Ma, Chi (Society for Leukocyte Biology, 2012)
Recent studies show that the liver is a preferred organ for the accumulation of MDSC. In this study, we examined the effect of systemic RB6-8C5 treatment on hepatic MDSC in tumor-bearing mice. EL4 tumor-bearing mice were injected i.p. with RB6-8C5, and hepatic, splenic, and blood MDSCs were analyzed by flow cytometry. Unexpectedly, hepatic MDSC remained in the liver, although RB6-8C5 completely eliminated them from the spleen and peripheral blood 24 h after treatment. Secondary antibody staining confirmed the presence of RB6-8C5-bound MDSC in the liver of mice with s.c. tumors. Similar observations were made in two other (colon and melanoma) tumor models. Whereas RB6-8C5 injection induced cell death of hepatic MDSC, as shown by Annexin V/7-AAD staining, these cells were replaced immediately, leading to a constant, increased frequency of hepatic MDSC. Adoptively transferred MDSC migrated preferentially to the liver after RB6-8C5 treatment, suggesting that hepatic MDSCs are reconstituted rapidly after depletion. Finally, hepatic MDSC remained immunosuppressive despite RB6-8C5 injection. Our study demonstrates that RB6-8C5 is not suitable for depletion of hepatic MDSCs and analysis of their function.